Orbital emphysema and medial orbital wall fracture after nose-blowing: a case report and review of literature - Suennen, Nathalie; Engert, Tobias (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Nose-blowing is commonly known as the harmless act of expelling nasal mucus by exhaling forcefully through the nose. We report a case of orbital emphysema in a 49-year-old female patient, who suffered from fractures of the medial orbital wall after forcefully blowing her nose. The patient presented to our emergency department with acute right sided periorbital swelling and pain as well as an unremarkable endoscopic examination of the nose. Prior to the event, a common cold with signs of acute sinusitis had been reported. A trauma to the eye was credibly denied, which is consistent with the medical imaging pattern. A CT-scan confirmed the diagnosis and showed air trapped into the orbit as well as multiple fractures of the lamina papyracea with displaced bone fragments. Visual acuity and extraocular muscle motility were intact. The patient was treated conservatively with prophylactic antibiotics and was instructed not to blow her nose. Follow-up examination after seven days showed a complete remission.